Prognosis Survey of Endodontic Treatment in Special Needs Patients - KITA, Shintaro; TAKAHIRA, Kiyomi; MIMURA, Kyouko; KAWAZOE, Tomoko; SAITOU, Hidefumi; MATSUNOBU, Rina; TARA, Tatsuo; INOMOTO, Takuyo; OSADA, Yutaka; YOSHIDA, Satoshi (Journal of the Japanese Society for Disability and Oral Health, 2020)
Many special needs patients who are maladapted to dental treatment have difficulty undergoing endodontic treatment in particular.The purpose of this study was to investigate the prognosis of endodontic treatment in special needs patients. Among the special needs patients who visited our dental clinic during the three-month period from December 2019 to February 2020, those who had received endodontic treatment at our dental clinic in the past were studied, and the prognosis was judged from clinical findings and radiological findings. The subjects were 150 teeth of 48 patients (average age 47.3±12.0 years). The diagnosis was pulpitis in 61 (40.7%) and apical periodontitis in 89 (59.3%). By disorder, there were 15 persons with intellectual disability (31.3%), 11 persons with autism spectrum disorder (22.9%), 7 persons with sequelae of cerebrovascular disorder (14.6%), and others including cerebral palsy, Down syndrome, and psychiatric disorders. Behavioral adjustment included 13 physical restraints (27.1%) and 4 intravenous sedation (8.3%). The number of teeth judged to have a good prognosis was 136 (90.7%)：pulpitis 96.7% and apical periodontitis 86.5%. Of the patients with apical periodontitis, 38 (63.3%) had apical transmission loss after treatment, and 8 (13.3%) had reduced size.As a result of a prognostic survey on endodontic treatment in special needs patients, the results were as good as those reported in healthy subjects. It seems to be possible to maintain oral health in special needs patients for a long time by faithfully carrying out accurate endodontic treatment rather than simply extracting the tooth because of failure or difficulty of treatment.